2018
DOI: 10.1136/injuryprev-2018-042945
|View full text |Cite
|
Sign up to set email alerts
|

Fatal drowning in the Western Cape, South Africa: a 7-year retrospective, epidemiological study

Abstract: IntroductionDrowning is a neglected public health threat in low-income and middle-income countries where the greatest drowning burden is observed. There is a paucity of drowning surveillance data from low-resource settings, particularly in Africa. Understanding local epidemiological factors will enable the development of context-specific drowning prevention initiatives and the appropriate allocation of resources.AimThe primary aim of this study was to describe the epidemiology of fatal drowning in the Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
4
16
0
Order By: Relevance
“…The WHO recently highlighted drowning as a major but neglected public health threat worldwide, killing approximately 320 000 people annually 1. Data on drowning from Africa are limited and mostly from South Africa 2–4. Of the few non-South African studies contributing drowning data over the past 30 years,5–10 most were not specifically designed to evaluate drowning but examined causes of injury or death more generally 5–9.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO recently highlighted drowning as a major but neglected public health threat worldwide, killing approximately 320 000 people annually 1. Data on drowning from Africa are limited and mostly from South Africa 2–4. Of the few non-South African studies contributing drowning data over the past 30 years,5–10 most were not specifically designed to evaluate drowning but examined causes of injury or death more generally 5–9.…”
Section: Introductionmentioning
confidence: 99%
“…Three (3) studies reported drowning in multiple sites (countries) [20,21,22]. Twenty-four (57%) of the articles originated from South Africa [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43], three (7.1%) were from Ethiopia [20,44,45], Ghana [20,46,47], Malawi [20,48,49], Nigeria [50,51,52] and Uganda [53,54,55] respectively, while 2 (4.8%) studies were from Cote d’Ivoire [20,56], Kenya [20,57] and Egypt [21,22] respectively. One (2.4%) article each originated from Burkina Faso [20], Guinea [58], The Gambia [20], Tanzania [59], Seychelles [60] and Zimbabwe [61], See Figure 1 for location.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used data were surveillance data (46%) and death registers including hospital, police and coronial reports. Twelve (12) studies investigated and described drowning exclusively [21,22,23,24,25,26,27,30,43,50,54,60], while in 30 studies, drowning was reported as part of a wider study including studies investigation all cause of death and external causes of death [20,28,29,31,32,33,34,35,36,37,38,39,40,41,42,44,45,46,47,48,49,51,52,53,55,56,57,58,59,61]. Measures used to describe drowning were proportions and rates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations